2007
DOI: 10.1177/089686080702700518
|View full text |Cite
|
Sign up to set email alerts
|

A Quarter of a Century of Adult Peritoneal Dialysis-Related Peritonitis at an Australian Medical Center

Abstract: Background Peritonitis remains one of the major complications of peritoneal dialysis (PD) and results in reduced technique survival and increased patient morbidity and mortality. Methods We prospectively recorded comprehensive data on all episodes of PD peritonitis over a 25-year period, including organisms isolated and antibiotic sensitivities. Data on 1588 PD patient-years with 2073 episodes of peritonitis were analyzed; 2089 organisms were isolated in 608 patients. Peritoneal dialysis technique and patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 36 publications
2
14
0
1
Order By: Relevance
“…; Brown et al . ). As peritonitis episodes decrease, the clinical outcomes improve as demonstrated by The Aus/NZ Registry (Brown et al .…”
Section: Planning and Developing A Pd Unitmentioning
confidence: 97%
See 1 more Smart Citation
“…; Brown et al . ). As peritonitis episodes decrease, the clinical outcomes improve as demonstrated by The Aus/NZ Registry (Brown et al .…”
Section: Planning and Developing A Pd Unitmentioning
confidence: 97%
“…In addition, protocols including proper catheter placement, careful training of patients with periodic retraining, particularly after episodes of infection and/or at each home or clinic visit, thorough hand washing with complete drying, and aggressive treatment of exit-site infection can significantly reduce PD-related infections (Bender et al 2006;Brown et al 2007). As peritonitis episodes decrease, the clinical outcomes improve as demonstrated by The Aus/NZ Registry (Brown et al 2007).…”
Section: Infection Controlmentioning
confidence: 99%
“…Due to improvements in connectology, peritonitis, a common and serious complication of PD, has decreased dramatically (Daly et al 2001 , 2014 ). Over the past several decades, the role of peritonitis as an independent risk factor for mortality and technique failure in PD patients has been well established (Brown et al 2007 ; Davenport 2009 ; Fried et al 1996 ; Kavanagh et al 2004 ; Mizuno et al 2011 ). However, recent studies on this topic have shown contradictory results (Fang et al 2008 ; Isla et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…A major complication of PD is the development of PD-associated peritonitis, primarily caused by bacterial infections within the abdomen. The definition of PD peritonitis has been standardized and requires two or more of the following criteria: cloudy dialysate fluid and/or abdominal pain and/or fever, dialysate white cell count of >100/μL with >50% neutrophils, or positive culture of dialysate fluid [ 7 ]. PD peritonitis occurs approximately once in every 19–28 patient months on treatment [ 2 ], and is associated with reduced modality and patient survival [ 8 11 ].…”
Section: Introductionmentioning
confidence: 99%